S64 The Cost of Refractory Asthma in the UK - a Preliminary Analysis. (19th November 2012) - O'Neill, S; Sweeney, J; Neill, C O; Brightling, C; Menzies-Gow, A; Niven, R; Chaudrai, R; Bucknall, C; Mansur, A; Patterson, C
Abstract : Introduction: Refractory asthma poses a potentially significant burden in terms of healthcare costs. Relatively little is known about the cost of treatment or what factors explain variations in treatment costs. This study uses data from the British Thoracic Society (BTS) Difficult Asthma Registry to estimate the healthcare costs associated with a sample of well-characterised refractory asthmatics and examines the role of a range of factors in explaining variations in healthcare. Methods: In this analysis data were extracted from the Registry on 689 patients and examined healthcare utilisation including all prescribed medicines, hospital inpatient stays, ITU stays, A&E/GP visits and CT scans over a 12 month period prior to the patient first being assessed at the specialist clinics. Patient characteristics included age, gender, lung function, clinical centre were care was provided, adherence status, BMI and whether or not the patient was on maintenance oral steroids. Unit costs were based on standard published sources. Costs were examined by category with respect to patient characteristics and total cost with respect to patient characteristics in multivariate regression analyses. Results: Mean total treatment cost among refractory asthmatics ranged between £3, 402 (SD=2, 680) to £4, 234 (SD=£3, 036). In a comparator non-refractory group mean total cost ranged from £1, 944 (SD= £1, 728) and £2, 565 (£2, 065). Drug costs comprised approximately 58% of all costs in refractory asthmatics and approximately 55% in the non-refractory group. In the refractory group significant predictors of total costs were FEV1, clinical centre in which care was provided, maintenance oral steroids and BMI. Patients who were on maintenance steroids cost 48% more than those who were not. Patients who were morbidly obese cost approximately 23% more than those who were normal weight. Conclusion: Treating individuals with refractory asthma presents a significant cost to the health service. The role of maintenance steroids in cost is dramatic and may relate to the impact of steroid induced morbidity and warrants further investigation.